How Do We Know What Information Sharing Is Really Worth? Exploring Methodologies to Measure the Value of Information Sharing and Fusion Efforts - Jackson, Brian A. (RAND Corporation, 2014)
The sharing of intelligence and law enforcement information is a central part of U.S. domestic security efforts, yet there are concerns about the effectiveness of information-sharing and fusion activities and their value relative to the public funds invested in them. This report lays out the challenges of evaluating information-sharing efforts that seek to achieve multiple goals simultaneously; reviews past evaluations of information-sharing programs; and lays out a path to improving the evaluation of such efforts.